The representation of personal deixis in German religious texts - Abdurakhmonova , Rano (The Lingua Spectrum, 2025)
This article analyzes the linguistic and communicative features of personal deixis in German religious texts. In religious discourse, personal deixis—such as ich (I), du (you), and wir (we)—serves the function of establishing semantic and emotional connections. The study explores how these linguistic units function within the context of ideological content, spiritual influence, divine address, and religious exhortation. The article also examines the stylistic and pragmatic significance of deictic elements, revealing how they contribute to the logical and spiritual structure of religious texts.